Definitive Diagnosis of Hepatic Hemangioma by 99mTc Labeled Red Blood Cell SPECT and Comparative Analysis with Ultrasound - Sultana, Saleha; Perveen, Rahima; Reza, Sharmin; Alam, Sumaiya; Sultana, Tania; Islam, Urnas; Bailey, Shamsun Nahar; Parveen, Rumana; Islam, Md Saiful; Sultana, Nasreen (Bangladesh Journal of Nuclear Medicine, 2024)
Introduction: Hemangiomas are the most common benign tumors of the liver. Accurate diagnosis is crucial for differentiating hemangioma from other space-occupying lesions (SOLs) as management strategies differ significantly. Though FNAC is the gold standard investigative tool for the diagnosis of hepatic hemangioma, newer modalities like 99mTc labeled RBC liver SPECT now is being emerging diagnostic tool for tailoring the treatment of the patient with hepatic hemangioma. Objective: This study aims to evaluate the diagnostic performance of 99mTc labeled RBC liver SPECT over ultrasound in the definitive diagnosis of hepatic hemangiomas. Patients and Methods: A retrospective observational study of 52 patients was conducted who underwent both 99mTc labeled RBC liver SPECT scan and USG for hepatic lesion evaluation at NINMAS Dhaka from the period of 2022 to 2023. High-resolution ultrasonography was performed. Diagnostic measures, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated for 99mTc labeled RBC SPECT and compared with USG. Imaging protocols, demographic data, and clinical characteristics were systematically analyzed. Results: Among 52 patients females were predominant. Representative images highlighted the enhanced blood pool activity in hepatic hemangiomas detected by RBC liver SPECT, which demonstrated superior sensitivity (92.3%) compared to ultrasound (76.9%). The specificity, positive predictive value (PPV), and overall accuracy were also higher for 99mTc labeled RBC SPECT and demonstrated significantly higher sensitivity (92.3%) compared to ultrasound (76.9%), with superior specificity, PPV, and overall accuracy. Conclusion: 99mTc labeled red blood cell liver SPECT holds a superior sensitivity and overall accuracy compared to ultrasound. It contributes to the evolving landscape of hepatic imaging and emphasizes the potential clinical utility of nuclear medicine techniques in the definitive diagnosis of hepatic lesions and also affects the clinical outcomes. Bangladesh J. Nuclear Med. 27(1): 69-74, 2024